Agriculture of Kuzbass Region in Early 1920s: Features of Development in Context of Agrarian Policy of RCP (b) and Consequences of Civil War - A. Yu. Karpinets; M. G. Leukhova (Научный диалог)
The article is devoted to the characterization of the crisis in the agriculture of the Kuzbass region in the early 1920s. Moreover, they are analyzed in the context of the consequences of the revolution and civil war. The issues of the dynamics of sown areas and animal husbandry in this territory are considered. Based on the analysis of statistical data, the volumes and structure of the peasant plow and regional herd are presented. The question is raised about the correlation of natural, climatic and socio-political factors in the conditions of the agricultural crisis of the early 1920s. The novelty of the study is that for the first time based on the processing of statistics, the state and dynamics of the main agricultural sectors in the Kuzbass region (Kuzbass) in the specified period are presented. The relevance of the study is due to its scientific and social significance. The first is determined by the fact that this kind of research, based on the analysis of statistical data, is carried out for the first time. The second is connected with the need to draw attention to the problems of sustainable socio-economic development of rural territories at present.